Arbitrage in the Foreign Exchange Market: Turning on the Microscope - Q. Farooq Akram; Dagfinn Rime; Lucio Sarno (Norges Bank, 2007)
This paper provides real-time evidence on the frequency, size and duration of arbitrage opportunities and deviations from the law of one price (LOP) in the foreign exchange market. We investigate deviations from the covered interest rate parity (CIP) condition ('round-trip arbitrage') and inter-market price differentials ('one-way arbitrage') using a unique data set for three major capital and foreign exchange markets that covers a period of more than seven months at tick frequency. The analysis unveils that: i) numerous short-lived violations of CIP and the LOP arise; ii) the size of CIP violations can be economically significant across exchange rates; iii) their duration is, on average, high enough to allow agents to exploit them, but low enough to explain why such opportunities have gone undetected in much previous research using data at lower frequency.
hdl:11250/2498432
Keywords: F31; F41; G14; G15; 330; exchange rates; arbitrage; covered interest rate parity; foreign exchange microstructure